Energy from the desert. Very large scale photovoltaic power--state of the art and into the future - Komoto, Keiichi (London : Routledge, Taylor & Francis Group, Earthscan from Routledge, 2013)
'This 4th volume in the established Energy From The Desert series examines and evaluates the potential and feasibility of Very Large Scale Photovoltaic Power Generation (VLS-PV) systems, which have capacities ranging from several megawatts to gigawatts, and to develop practical project proposals toward implementing the VLS-PV systems in the future. Comprehensively analysing all major issues involved in such large scale applications, based on the latest scientific and technological developments and by means of close international co-operation with experts from different countries. From the perspective of the global energy situation, global warming, and other environmental issues, it is apparent that VLS-PV systems can: contribute substantially to global energy needs; become economically and technologically feasible soon; contribute significantly to the global environment protection; contribute significantly to socio-economic development. Energy policies around the world are gradually changing direction to focus less on nuclear energy with the expectation to turn to denuclearization entirely with the negative impacts of nuclear energy, while in parallel the importance of and expectations for renewable energy technologies are increasing drastically as possible energy infrastructure, as well as environmental friendly technology. This book recognises that very large scale solar electricity generation provides economic, social and environmental benefits, security of electricity supply and fair access to affordable and sustainable energy solutions and that VLS-PV systems must be one of the promising options for large-scale deployment of PV systems and renewable energy technologies'--
Includes bibliographical references.
Keywords: Photovoltaic power generation; Photovoltaic power systems; Desert resources development